Primary Non Hodgkin Lymphoma on the left breast of a 53 year old woman: A rare case report (Research, Society and Development, 2023)
Primary breast lymphoma (PBL) is a rare but distinct subtype of extranodal lymphoma, comprising 0.5% of breast malignancies, approximately 1% of all non-Hodgkin's lymphomas (NHL) and